Thermodynamic scaling of relaxation: insights from anharmonic elasticity. (14th February 2017) - Bernini, S; Puosi, F; Leporini, D
Abstract: Using molecular dynamics simulations of a molecular liquid, we investigate the thermodynamic scaling (TS) of the structural relaxation time τ α in terms of the quantity T ρ − γ t s, where T and ρ are the temperature and density, respectively. The liquid does not exhibit strong virial–energy correlations. We propose a method for evaluating both the characteristic exponent γ t s and the TS master curve that uses experimentally accessible quantities that characterise the anharmonic elasticity and does not use details about the microscopic interactions. In particular, we express the TS characteristic exponent γ t s in terms of the lattice Grüneisen parameter γ L and the isochoric anharmonicity δ L . An analytic expression of the TS master curve of τ α with δ L as the key adjustable parameter is found. The comparison with the experimental TS master curves and the isochoric fragilities of 34 glassformers is satisfying. In a few cases, where thermodynamic data are available, we test (i) the predicted characteristic exponent γ t s and (ii) the isochoric anharmonicity δ L, as drawn by the best fit of the TS of the structural relaxation, against the available thermodynamic data. A linear relation between the isochoric fragility and the isochoric anharmonicity δ L is found and compared favourably with the results of experiments with no adjustable parameters. A relation between the increase of the isochoric vibrational heat capacity due to anharmonicity and the isochoric fragility is derived.